Global UN initiative on sustainable energy development and climate change (International relations and international law Journal, 2016)
This article is about the UN global initiative on sustainable energy development and climate change. The author analyze the activity of the UN, which is a driving factor in the responses to the global challenges of humanity, as well as a special Advisory Group of Experts on Energy and Climate Change, which was established in 2009 by the UN Secretary General. The Group’s activities is unique in that it is composed of high level representatives of key organizations ofthe UN system - UNIDO, UNDP, UNEP, the UN Foundation, the UN Framework Convention on Climate Change and others, the Global Environment Facility; international organizations (World energy Council, the International Atomic Energy Agency, etc.). Much attention is paid to the initiatives of President N.Nazarbayev “Green Bridge” and “Global Energy Strategy for Sustainable Development in the XXI century”.
Keywords: United Nations; the initiative of the Republic of Kazakhstan; “Rio 20”; Sustainable Development; climate change; “Green Bridge”; energy development